Existence of paddy fields in Makassar city as a part of green open space: Ecological perspective on urban farming. Issue 2 (July 2021) - Yanti, C W B; Ala, A; Dungga, N E; Arif, S
Abstract: Paddy fields are part of urban green open space which is now rarely found in big cities because it has been converted into built-up land. This study aims to study the existence of paddy fields in Makassar City in 2019 and to review their ecological function in CO2 absorption. Spatial analysis using the GIS method was used to map paddy fields that are still productive in 2019 in Makassar City. Analysis of CO2 uptake from the rice cultivation in this urban paddy fields was carried out using allometric equations. Mapping results show that recently, there are 1, 473.58 hectares of paddy fields in Makassar City. These paddy fields are spread across seven districts, namely Tamalate, Rappocini, Tallo, Panakukkang, Manggala, Biringkanaya and Tamalanrea. Makassar City must provide a minimum of 5, 273 ha of green open space. The existence of this paddy field contributes about 8.38% of the total minimum required green open space (30%) for Makassar City. The paddy fields in Makassar City, planted with rice as much as one to two times a year, will be able to absorb CO2 in the range of 5, 814.16 to 10, 243 tons per year. Thus, the existence of paddy fields in urban areas needs to be maintained to improve the quality of the urban environment.